Antibiotic residues in surface water and urban water supply and their health risk in a suburban district of Hangzhou municipality, 2023 - Yuwei HONG; Jiangbo LI; Lidan JIANG; Dandan LIU; Junlin WANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo detect antibiotic residues in surface water and urban water supply and assess health risk of the antibiotic residues in a suburban district of Hangzhou municipality, Zhejiang province. MethodsTotally 38 surface water samples were collected from 19 sampling points along the Fuchun River Basin and 58 tap water samples were collected at 29 sampling points of a urban water supply system in a suburban district of Hangzhou municipality during February - March 2023. The residues of 52 antibiotics of 6 categories in the samples of surface water and urban water supply were detected by ultra-performance liquid chromatography-tandem mass spectrum (UPLC-MS/MS) after solid-phase extraction (SPE). Then we assessed ecological and human health risk correlated with the antibiotic residues detected using risk quotient (RQ ) method.ResultsThe residues of 25 kinds of antibiotics were detected in the surface water samples, and the concentrations of the residues ranged from not detected (ND) to 463.66 ng/L; for the samples of the urban water supply, residues of 6 kinds of antibiotics were detected, with the residue ranges and detection rates of ND - 0.72 ng/L and 93.10% for sulfapyridine, ND - 1.16 ng/L and 86.21% for sulfachloropyridazine, ND - 0.60 ng/L and 6.90% for erythromycin, ND - 0.75 ng/L and 27.59% for clarithromycin, ND - 0.68 ng/L and 34.48% for roxithromycin, and ND - 0.96 ng/L and 86.21% for anhydroerythromycin, respectively. The range of RQ in ecological risk assessment was 0 - 10.56 for the detected residues of 25 antibiotics in the surface water samples and the detected antibiotics with higher ecological risk were sulfadiazine, oxytetracycline, erythromycin, clarithromycin, and anhydroerythromycin. The range of RQ in health risk assessment was 4.45 × 10 - 7 - 1.68 × 10 - 4 for the detected residues of 6 antibiotics in the tap water samples and there was no significant health risk relevant to the detected antibiotics. ConclusionIn a suburban district of Hangzhou municipality, the residues of a number of antibiotics were detected and the residues of sulfadiazine, oxytetracycline, erythromycin, clarithromycin and anhydroerythromycin could result in ecological risks; only trace residues of some antibiotics were detected in tap water samples from urban water supply and the residues were at the levels won't cause obvious human health risk.